2016
DOI: 10.1016/j.wasman.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of plastic waste: Presence of phthalates in plastics from households and industry

Abstract: Plastics recycling has the potential to substitute virgin plastics partially as a source of raw materials in plastic product manufacturing. Plastic as a material may contain a variety of chemicals, some potentially hazardous. Phthalates, for instance, are a group of chemicals produced in large volumes and are commonly used as plasticisers in plastics manufacturing. Potential impacts on human health require restricted use in selected applications and a need for the closer monitoring of potential sources of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 42 publications
(48 reference statements)
0
81
0
3
Order By: Relevance
“…As very few studies and data related to chemical contamination of plastic waste exist (Pivnenko et al. ; Ballesteros‐Gómez et al. ; Whitt et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As very few studies and data related to chemical contamination of plastic waste exist (Pivnenko et al. ; Ballesteros‐Gómez et al. ; Whitt et al.…”
Section: Methodsmentioning
confidence: 99%
“…All MRF outputs from the 84 scenarios were classified into one of the three quality levels. As very few studies and data related to chemical contamination of plastic waste exist (Pivnenko et al 2016;Ballesteros-Gómez et al 2014;Whitt et al 2012;Riber et al 2009;Ernst et al 2000;Huber and Franz 1997), it was not feasible to include chemical contamination in the assessment. Therefore, the classification was carried out based solely on the presence of physical impurities, including both non-plastic and non-target polymer impurities.…”
Section: Quality Classificationmentioning
confidence: 99%
“…Di-iso-butyl phthalate (DiBP), di-(ethylhexyl) phthalate (DEHP) and dibutyl phthalate (DBP) are LMW phthalates found in the majority of plastics (Pivnenko, 2016). DEHP is the dominant phthalate found in relatively high concentrations (up to 2700 mg/kg) in the majority of the plastic samples.…”
Section: 1mentioning
confidence: 99%
“…DEHP is the dominant phthalate found in relatively high concentrations (up to 2700 mg/kg) in the majority of the plastic samples. Several sources of plastics were evaluated for their phthalate content (Pivnenko et al, 2016). The results showed that virgin and recycled industrial plastics (group 1) have similar phthalate content.…”
Section: 1mentioning
confidence: 99%
“…In another study, Fukushima et al (2010) investigated study on dechlorination technology for municipal waste plastics containing polyvinyl chloride and polyethylene terephthalate. Pivnenko et al (2016) studied recycling of plastic waste: presence of phthalates in plastics from households and industry. There is a need for further studies on waste thermoplastics recycling.…”
Section: Introductionmentioning
confidence: 99%